PENINGKATAN HASIL BELAJAR SISWA MATERI MENJELASKAN SIFAT OPERASI HITUNG PADA BILANGAN CACAH DENGAN MODEL PEMBELAJARAN BERTUKAR PASANGAN - Ai Haryatin (Universitas Pakuan, 2021)
IMPROVING STUDENT LEARNING OUTCOMES THE MATERIAL EXPLAINS THE NATURE OF COUNTING OPERATIONS ON WHOLE NUMBERS WITH THE PAIR EXCHANGE LEARNING MODELThe research was conducted by observing in the classroom that the low quality of learning Mathematics can have an effect on student learning outcomes. Therefore, a teacher needs to consider an effective and fun learning model so that it can improve student learning outcomes. One of the learning approaches that was tried through this research was the application of the Pair Exchange learning model. The research was conducted in class IIIA of SDN Kampung Sawah, Bogor City and aimed (1) to find out through the Pair Exchange Learning Model that it can improve students' learning outcomes about Explaining the Nature of Counting Operations on Whole Numbers in Mathematics subjects (2) To describe the Pair Exchange Learning Model about Explaining the Properties of Counting Operations on Whole Numbers in Mathematics (3) To measure how much increase in student learning outcomes about Explaining the Properties of Counting Operations on Whole Numbers is applied after the Pair Exchange Learning Model is applied in Mathematics The results of this study indicate that by using the Pair Exchange learning model especially about Explaining the Properties of Counting Operations on Whole Numbers in class III A at SD Negeri Kampung Sawah, Bogor City, the average student learning outcomes increased to 71.43 in Cycle I and 96.43 in Cycle II. From the description above, the researcher concludes that the Pair Exchange learning model applied by the teacher can improve student learning outcomes, therefore the researcher suggests that the use of the Pair Exchange learning model be socialized and used as an alternative in learning Mathematics in schools in the Bogor City Education Office.